The Students - Mahendra, M Yusril (Journal Of Foreign Language Learning and Teaching, 2021)
Nowadays, listening to music is an activity favored by young people. There is lots of music streaming applications that can help them listen to music anywhere. Joox is a music streaming application used by young people to listen to music. Some of them use Joox to listen to inter-local music. Not only providing audio, Joox also provides the lyrics for the song. These services can be an interesting way to improve vocabulary and listening skills. Some learners find it difficult to capture vocabulary when they are listening to audio.The purpose of this study was to determine student perceptions regarding the use of Joox as a learning method that is used in addition to outside of classroom in increasing self-motivation towards learning English, especially in listening, The statements that given are about the impact of using Joox to their vocabulary and listening skill using likert scale. The result of questionnaire revealed that students have positive perception toward the use of Joox in enhancing their vocabulary and listening.This research used quantitative and qualitative methods in data collectionwith a purposive sampling technique. Data were analyzed with SPSS 20 to get standard deviations, averages, and medians. The population of this research was the 2017 English language students at IAIN Palangka Raya. 40 students as samples to answered questionnaire questions to complete the research objectives. 5 students as the main speakers in the interview to explain more deeply about the student perception about Joox in listening skill. To collect data, researchers used questionnaires and interviews.This research will explain more about how effective the use of Joox outside the classroom is using the Joox application. The main research findings show that: (1) Students was motivated to learn English when used Joox app because Joox provider lyric, student can listen song meanwhile listen song. (2) Students had positive perception on using Joox because they think used Joox not only improve their listening skill but also practice their pronunciation. (3) Student feel their listening skill engaged after used Joox app and enrich their vocabulary through listen song. effects in using Joox as a learning tool that can motivate listening skills.